2021
DOI: 10.1007/s11708-021-0749-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-economic analysis of a direct supercritical CO2 electric power generation system using geothermal heat

Abstract: A comprehensive thermo-economic model combining a geothermal heat mining system and a direct supercritical CO 2 turbine expansion electric power generation system was proposed in this paper. Assisted by this integrated model, thermo-economic and optimization analyses for the key design parameters of the whole system including the geothermal well pattern and operational conditions were performed to obtain a minimal levelized cost of electricity (LCOE). Specifically, in geothermal heat extraction simulation, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Generally, the heat production performance of CO 2 -EGSs is significantly better than that of water-EGSs, especially for geothermal reservoirs with lower permeability [18,19]. Pan et al [20,21] used supercritical CO 2 as the working fluid to study geothermal production potential using the T2WELL code (e.g., a wellbore-reservoir coupled model). Their results showed that a good thermosiphon effect was achieved when using CO 2 as the working fluid, thus significantly reducing the external cost for pumping.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the heat production performance of CO 2 -EGSs is significantly better than that of water-EGSs, especially for geothermal reservoirs with lower permeability [18,19]. Pan et al [20,21] used supercritical CO 2 as the working fluid to study geothermal production potential using the T2WELL code (e.g., a wellbore-reservoir coupled model). Their results showed that a good thermosiphon effect was achieved when using CO 2 as the working fluid, thus significantly reducing the external cost for pumping.…”
Section: Introductionmentioning
confidence: 99%